Fontes e profundidades de aplicação de fósforo na cultura do milho - Pizzatto, Idianara Fernanda (2021)
Phosphorus is one of the nutrients applied in larger quantities in agriculture, given its widespread lack and low availability in the soil, caused by its strong affinity with iron (Fe) and aluminum (Al) oxides, forming compounds with low solubility. In this sense, the present work had as general objective to evaluate the corn crop yield as a function of phosphorus sources and application methods, during the 2018/2019 and 2019/2020 harvests. Three phosphate sources were tested: single superphosphate, Top-Phos® and reactive rock phosphate, plus a control treatment without P supply, evaluating four application methods (surface broadcast and seed furrow application at 5.0; 8.0 and 11.0 cm in depth). A randomized block design, in a factorial scheme, consisting of 12 treatments + control treatment, with four replications, was used. During sowing, the plantability parameters were evaluated: maximum furrow width, mobilized soil area and sowing depth. For corn crop, the following were evaluated: initial and final plant stands, initial and final plant height, initial and final stem diameter, ear insertion height, number of grain rows per ear, number of grains per row, mass thousand grains and productivity. For the fractionation of P, to determine P-resin and P-total, samples were collected at a depth of 0.0-15.0 cm, stratified into three subsamples at depths of 0.0-5.0 cm, 5, 0-10.0 cm and 10.0-15.0 cm. The results were submitted to analysis of variance by the F test at a significance of 5% probability, using the statistical program GENES®. The determination of P-resin and P-total did not show statistical differences regarding the sources of phosphorus fertilization and the fertilization depths. Greater sowing depths were observed when the fertilizer was applied at greater depths. In the 2018/2019 harvest there were significant differences, only when the fertilizer was deposited at 11.0 cm. For the 2019/2020 season, the fertilization depth of 8.0 cm did not present significant differences in relation to the depth of 11.0 cm in depth, presenting higher averages. For the furrow surface width, in both crops evaluated, there were no significant differences in relation to the different fertilization depths, for mobilized soil area higher values were observed for the fertilization depth of 11.0 cm in both crops. Better productivity in corn crop in the 2018/2019 harvest was verified for treatments that received application of simple superphosphate. For the 2019/2020 harvest there were no significant differences between the sources of phosphate fertilization. There were no significant differences between the sources of phosphate fertilization compared to the control treatment in the final yield of the corn crop.